2008
DOI: 10.1074/jbc.m800358200
|View full text |Cite
|
Sign up to set email alerts
|

The ATP-gated P2X1 Receptor Plays a Pivotal Role in Activation of Aspirin-treated Platelets by Thrombin and Epinephrine

Abstract: Human platelets express protease-activated receptor 1 (PAR1) and PAR4 but limited data indicate for differences in signal transduction. We studied the involvement of PAR1 and PAR4 in the cross-talk between thrombin and epinephrine. The results show that epinephrine acted via ␣ 2A -adrenergic receptors to provoke aggregation, secretion, and Ca 2؉ mobilization in aspirin-treated platelets pre-stimulated with subthreshold concentrations of thrombin. Incubating platelets with antibodies against PAR4 or the PAR4-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 36 publications
1
39
0
Order By: Relevance
“…Therefore, we conclude that PR3 stimulates shape change of human platelets through activation of the Rho/Rho kinase and Ca 2+ signaling pathways. It is well established that adrenaline enhances platelet activation by other, more efficient activators [27]. We found that adrenaline reinforced platelet shape change by PR3 but this was not followed by aggregation.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Therefore, we conclude that PR3 stimulates shape change of human platelets through activation of the Rho/Rho kinase and Ca 2+ signaling pathways. It is well established that adrenaline enhances platelet activation by other, more efficient activators [27]. We found that adrenaline reinforced platelet shape change by PR3 but this was not followed by aggregation.…”
Section: Discussionmentioning
confidence: 49%
“…There is a large body of evidence that positive modulators, such as adrenaline, facilitate for secretion and aggregation when platelets are subsequently exposed to strong activators like thrombin, ADP and collagen [26,27]. However, PR3 was not shown to alter activation of the fibrinogen receptor in response to thrombin, PAR1-or PAR4-activating peptides at any concentrations, nor did it change the magnitude of ADP-induced aggregation (in the absence of apyrase).…”
Section: Discussionmentioning
confidence: 99%
“…We then studied ATP inhibition of NK chemotaxis to CX 3 CL1 in the presence of NF157, or MRS2159 and NF023, 2 different P2X 1 inhibitors. [19][20][21][22] Although NF157 restored NK chemotaxis abolished by ATP, neither MRS2159 nor NF023 modified NK-cell migration to CX 3 CL1 in the presence of ATP ( Figure 5A). Similarly, NK-cell killing of HUVECs that was elicited by CX 3 CL1 and blocked by ATP was restored by NF157 but not by P2X 1 antagonists ( Figure 5B).…”
Section: Inhibition Of Nk-cell Response To CX 3 Cl1 Is Mediated By Thmentioning
confidence: 99%
“…Activation of platelet by the thrombin mimetic hexapeptide SFLLRN was marginally affected by aspirin and clopidogrel treatments. This is probably explained by the efficiency of thrombin receptors in inducing intracellular signaling [32]. Specifically, this means that thrombin activation of platelets does not rely on secondary positive feed-back loops such as thromboxane A2 and ADP.…”
Section: Discussionmentioning
confidence: 99%